CD44v6-O-MWNTS-Loaded Gemcitabine and CXCR4 siRNA Improves the Anti-tumor Effectiveness of Ovarian Cancer - Yin, Wen; Qian, Su-Min (Frontiers in Cell and Developmental Biology, 2021)
Ovarian cancer is one of the most common malignancies of the female reproductive system and the deadliest gynecologic cancer. CXCR4 is expressed in a variety of malignant tumors such as breast, prostate and ovarian cancers, and is closely related to the migration, invasion and metastasis of tumor cells. Carbon nanotubes have great potential for targeted therapy of tumors. CD44v6 is not expressed in normal ovarian tissues but is highly expressed in ovarian epithelial carcinoma. In the present study, we applied small interfering RNA targeting CXCR4 gene and the clinical treatment gemcitabine and oxaliplatin of ovarian cancer as the therapeutic drug, and organically integrated chemotherapy and gene therapy through carbon nanotubes, and used CD44v6 single chain antibody as the targeting moiety to explore its application in ovarian cancer treatment. Significantly, we successfully synthesized CD44v6-O-MWNTS/Gemcitabine/1,2-dioleoyl-3-trimethylammonium-propane (DOTAP)/siRNA system and the results were observed by transmission electron microscope (TEM) and scanning electron microscope (SEM). CD44v6-O-MWNTS/Gemcitabine/DOTAP was able to fully load siRNA at the ratio of 1:2.5. The carbon nanotubes could protect the siRNA. The drug release analysis showed that O-MWNTS/drug/DOTAP/siRNA was able to effectively release the siRNA, and gemcitabine or oxaliplatin in a time-dependent manner. O-MWNTS/drug/DOTAP/siRNA was able to be effectively uptake by ovarian cancer cells. The cellular uptake of CD44v6-O-MWNTS/drug/DOTAP/siRNA was mainly depended on lipid raft-mediated endocytosis. CD44v6-O-MWNTS/drug/DOTAP/siRNA improved the effect of siRNA on the inhibition of ovarian cancer cell viability and the induction of cell apoptosis. The expression of CXCR4 was decreased by CD44v6-O-MWNTS/drug/DOTAP/siRNA in ovarian cancer cells. Tumorigenicity analysis in nude mice showed that CD44v6-O-MWNTS/drug/DOTAP/siRNA significantly repressed the tumor growth of ovarian cancer cells in vivo. The levels of Ki-67 and CXCR4 were repressed by CD44v6-O-MWNTS/drug/DOTAP/siRNA in the system. Thus, we concluded that the obtained CD44v6-O-MWNTS could effectively load gemcitabine or oxaliplatin, and CXCR4 siRNA, internalized by cancer cells and realized notable in vitro and in vivo inhibitory function against ovarian cancer growth. Our study provided a promising nanomaterial for co-delivery of siRNA and anti-tumor drug for the therapy of ovarian cancer.